Perancangan Sistem Informasi Penggajian Karyawan Menggunakan Metode Scrum - Aulianita, Rizki; Mukhayaroh, Anna (INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS : Journal of Information Management; Vol 11 No 1 (2026): INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS (JUNI 2026)DO - 10.51211/imbi.v11i1.3889, 2026)
The current information system is one of the evidences of the development of the digital world. This also applies to the industrial sector, with the implementation of a payroll information system in companies. PT KBB is a company engaged in the service sector. In its payroll activities there still uses a semi-computerized system so that as a result the recording is still prone to errors, decision making is not based on careful calculations and often errors in calculating employee salaries. This study aims to design a website-based payroll information system so that employee salary data management becomes more valid, effective and payroll can be carried out according to the specified deadline. The software development method used in this study is Agile. The results of this study are that the web-based Employee Payroll Information System can be implemented well, making it easier for HRD to manage employee absences, calculate employee salaries to the Payroll Reporting process   Keywords : Information Systems, Payroll, Agile